2005
DOI: 10.1111/j.1464-5491.2005.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic inequalities in the prevalence of Type 2 diabetes, cardiovascular risk factors and chronic diabetic complications in the Basque Country, Spain

Abstract: This study shows an association between deprivation and Type 2 diabetes prevalence, cardiovascular risk factors and chronic diabetic complications in Type 2 diabetes patients. Despite a greater use of health services by less wealthy patients, they showed worse glycaemic control and more chronic complications. Besides clinical variables, socio-economic status and environmental information need to be considered in the assessment of risk profile of diabetic patients by health professionals and by health service p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
71
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 24 publications
16
71
2
4
Order By: Relevance
“…In our study we observed that socioeconomic health was inversely related to the prevalence of diabetes, both for each country analysed individually and for the overall data. In accordance with other studies we have found that diabetes morbidity is associated with having a disadvantaged SEP [2,3,[8][9][10][11][12]. Previous studies that have analysed inequalities in diabetes mortality also have shown that people with a lower SEP have a higher risk of dying from diabetes [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study we observed that socioeconomic health was inversely related to the prevalence of diabetes, both for each country analysed individually and for the overall data. In accordance with other studies we have found that diabetes morbidity is associated with having a disadvantaged SEP [2,3,[8][9][10][11][12]. Previous studies that have analysed inequalities in diabetes mortality also have shown that people with a lower SEP have a higher risk of dying from diabetes [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
“…These factors are less access to and use of healthcare services and poorer quality of the care process, as well as lower levels of diabetes education and control of variables related to diabetes (e.g. glycaemia, weight, cholesterol) for patients that occupy a disadvantaged SEP [2,8,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A population-based, cross-sectional observational study with longitudinal analysis over 12 years conducted at East of Scotland by Liying Low et al showed that socioeconomic deprivation was associated with increased prevalence of diabetic retinopathy in patients with type 1 DM, but not in patients with type 2 DM (3) . In Spain, socioeconomic status was not independently associated with DR (4) . The fact that people belonging to the upper class were less affected could be due to the increased health awareness among patients and the readily accessible medical facilities so that they seek medical attention at the earliest than the people from deprived classes of the society.…”
Section: Discussionmentioning
confidence: 94%